The impact of objective urban features on perception of neighbourhood environments - Jiuling Li; Mohammad Javad Koohsari; Jing Zhao; Andrew T. Kaczynski; Gavin R. McCormack; Koichiro Oka; Tomoki Nakaya; Ryo Tanimoto; Reo Watanabe; Tomoya Hanibuchi (Scientific Reports)
Abstract Perceptions of the neighbourhood environment can play an important role in promoting public health, yet modifying perceptions is challenging. Adjusting the built environment may be a pathway to influence perceptions. In addition to the physical environment, intrapersonal factors may shape perceptions. This study analysed data from several Japanese major cities to explore the association between objective and perceived neighbourhood environment attributes, stratified by age and gender. Perceived neighbourhood environment measures were adapted from established scales, while objective measures were derived from participants’ geographic address data. Multivariate linear regression was employed to assess these associations. All objective measures were positively associated with overall neighbourhood environment perception, and destination diversity presented the strongest association. Perceptions among those 65–69 were more strongly influenced by the physical environments of their neighbourhood, whether positively or negatively. Objective environmental measures have a greater positive impact on perception for females than for males, while males are more negatively affected in terms of perceptions of crime and traffic safety. These findings highlight how objective built environment attributes may shape residents’ perceptions across different demographic groups.